ANTIFUNGAL ACTIVITY OF ESSENTIAL OILS FROM NATIVE TREE SPECIES IN SOUTHERN BRAZIL - Bianchini, Nadia Helena; da Silva, Daniela Thomas; Schindler, Bianca; Muniz, Marlove Fátima Brião; Heinzmann, Berta Maria (Floresta, 2022)
The objective of this exploratory work was to analyze the yield and chemical composition of essential oils (EO) from Blepharocalyx salicifolius [BS] and from two pools of EO obtained from Nectandra megapotamica [NM1 and NM2], as well as to evaluate their antifungal properties against the fungi Pycnoporus sanguineus (white-rot) and Gloeophyllum trabeum (brown-rot). The EO were obtained by hydrodistillation and its components were identified by gas chromatography coupled to mass spectrometry (GC-MS) and quantified with flame ionization detection (GC-FID). For the evaluation of antifungal activity, the mycelial growth index (MGI) and the mycelial growth inhibition (GI) of BS were determined at concentrations of 1, 2 and 5 µL.mL-1, and 0.25; 0.5 and 1 µL.mL-1 for MN1 and NM2. The yield of EOs was 2.29% (BS), 0.14% (NM1) and 0.17% (NM2). The major components of BS EO were eucalyptol (63.44%) and β-caryophyllene (13.68%), from NM1 were bicyclogermacrene (16.14%) and α-pinene (15.93%), and for NM2, α-pinene (19.04%) and sabinene (16.66%). EO NM1 (1μL.mL-1) showed the best result for antifungal activity, inhibiting about 57.55 ± 0.68 % of P. sanguineus growth and 58.82 ± 0.78 % in the test with G. trabeum.